Perancangan Perancangan Laporan Keuangan dan Perpajakan Berbasis Microsoft Excel Untung Mendukung Efisiensi Biaya Produksi Pada UMKM Ayam Geprek Miss Deppy: Perancangan Laporan Keuangan dan Perpajakan Berbasis Microsoft Excel Untung Mendukung Efisiensi Biaya Produksi Pada UMKM Ayam Geprek Miss Deppy - Febriyanti, Hadryah; Al Haitamy, Eri Bestary; Yuliansyah, Dwi Novrian (Journal of Applied Accounting And Business, 2026)
Ayam Geprek Miss Deppy MSMEs do not have a structured financial and tax recording system, making it difficult for business owners to know their financial condition and control production costs. This research aims to design financial and taxation reports based on Microsoft Excel in accordance with the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) to support production cost efficiency. The research method used is a descriptive qualitative method with data collection techniques through observation, interviews, and documentation. The data obtained was analyzed by designing a Microsoft Excel-based financial recording system which includes recording transactions, income statements, calculation of cost of production, and tax calculations. The results of the study show that the application of Microsoft Excel-based financial statements helps MSMEs in compiling financial statements more systematically and makes it easier to control production costs, thereby supporting business decision-making. Keywords: Financial Statements, Taxation, Microsoft Excel.